2021
DOI: 10.3892/etm.2021.9890
|View full text |Cite
|
Sign up to set email alerts
|

microRNA‑23 inhibits inflammation to alleviate rheumatoid arthritis via regulating CXCL12

Abstract: Rheumatoid arthritis (RA) is a common systemic, inflammatory and autoimmune disorder. MicroRNAs (miRs) are strongly associated with the initiation and progression of RA. However, the functions and mechanisms underlying miR-23 in RA are not completely understood. Therefore, the present study aimed to investigate the molecular mechanisms underlying miR-23 in RA. A bioinformatics tool (StarBase) and a wide range of experimental assays, including reverse transcription-quantitative PCR, western blotting, luciferase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…In general, the log-fold change (logFC) of CXCL12 in AADs was significantly higher than in NAADs ( p < 0.001, Figure 6A ). Accumulating evidence demonstrates that CXCL12 upregulation was implicated in AADs including IPF [ 51 ], rheumatoid arthritis (RA) [ 52 ], and amyotrophic lateral sclerosis (ALS) [ 53 ]. Consistent with our findings, upregulation of CXCL12 was suggested to promote migration and proliferation of human lung fibroblast in IPF as well as to enhance monocytes infiltration into the synovial tissue in RA [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the log-fold change (logFC) of CXCL12 in AADs was significantly higher than in NAADs ( p < 0.001, Figure 6A ). Accumulating evidence demonstrates that CXCL12 upregulation was implicated in AADs including IPF [ 51 ], rheumatoid arthritis (RA) [ 52 ], and amyotrophic lateral sclerosis (ALS) [ 53 ]. Consistent with our findings, upregulation of CXCL12 was suggested to promote migration and proliferation of human lung fibroblast in IPF as well as to enhance monocytes infiltration into the synovial tissue in RA [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Accumulating evidence demonstrates that CXCL12 upregulation was implicated in AADs including IPF [ 51 ], rheumatoid arthritis (RA) [ 52 ], and amyotrophic lateral sclerosis (ALS) [ 53 ]. Consistent with our findings, upregulation of CXCL12 was suggested to promote migration and proliferation of human lung fibroblast in IPF as well as to enhance monocytes infiltration into the synovial tissue in RA [ 51 , 52 ]. Treatment with an antagonist of CXCR4, the receptor for CXCL12, extended lifespan, improved motor function, and led to weight loss in ALS in vivo [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…miR-147 was shown to be engaged in inflammatory response induction, while its loss diminished joint inflammation in rats with pristine induced arthritis and reduced TNF-α, IL-6, MMP3, and MMP13 expression in vitro ( Jiang et al, 2021 ). Another study showed that microRNA 23 is engaged in RA pathogenesis by influencing the NF-κB signaling pathway and decreasing TNF-α, IL-1β and IL-8 expression in RA patients ( Gao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The levels of miR-548a-3p in serum exosomes and PBMCs of RA patients are significantly downregulated and negatively correlated with the levels of RF, ESR, and CRP, suggesting that the miR-548a-3p/TLR4/NF-κB axis could be used as a biomarker for RA diagnosis and targets for therapy ( 113 ). Serum exosome miR-1915-3p expression is significantly elevated in RA patients with clinical remission and negatively associated with CRP levels, which may be a potential biomarker of disease activity in Korean RA patients ( 114 ). Exosomes participate in cell-to-cell communication via the packaging and shuttling of diverse cargo molecules (including miRNAs) to recipient cells and have a crucial role in autoimmune-related disorders ( 115 , 116 ).…”
Section: Candidate Rnas As Biomarkers For Ramentioning
confidence: 99%